78‐3: Distinguished Paper: Vein Detection with Near‐infrared Organic Photodetectors for Biometric Authentication. Issue 1 (25th September 2020) - Tordera, Daniel; Peeters, Bart; Delvitto, Ezequiel; Shanmugam, Santhosh; Maas, Joris; de Riet, Joris; Verbeek, Roy; van de Laar, Robert; Bel, Thijs; Haas, Gerard; Ugalde, Leslye; van Breemen, Albert; et al.
Abstract : We combine a near‐infrared (NIR) sensitive organic photodetector with a high‐resolution 508 ppi oxide TFT backplane to create a large‐area thin NIR detector. Using a NIR light source the detector is capable of imaging the (pattern of) veins under the skin in reflection, leading to improved biometric authentication.